Changes in straight skating motions in world-class long-distance speed skaters during the ladies' 3,000-m race - Kimura, Y.; Yokozawa, T.; Maeda, A.; Yuda, J. (International Journal of Sport & Health Science, 2022)
The present study aimed to investigate kinematic changes in the straight skating motions of world-class speed skaters during a ladies' 3,000-m race. Sixteen elite skaters who participated in the World Cup were included in the study. Three-dimensional motion analyses using 4 synchronized high-speed cameras (300 Hz) were performed on the straight skating motions at the initial, middle, and final stages of the race. As the race progressed, skating velocity decreased and the body center of mass (CM) height and the thigh angle increased. Shank outward tilting time exhibited a significant negative relationship with the official time for both the left and right strokes in the initial stage. In the final stage, skating velocity was significantly, positively associated with hip and knee angular velocity at the end of strokes. These results demonstrated that, in the ladies' 3,000-m race, although the air resistance increases with higher CM position and the skating velocity decreases as the race progressed, the straight skating motion of the excellent skaters was characterized by longer outward tilting of the shank in the initial stage contributes to maintaining skating velocity until the middle and final stages of the race.